Clinical Study on Qinghuo Qibi Decoction Combined with Rehabilitation Training in the Treatment of Autism Spectrum Disorder of Heart-liver Fire Hyperactivity Pattern - Jiangwei Yang; Yaxiong Guo (Journal of Artificial Intelligence and Information, 2026)
Objective: To observe the clinical efficacy of Qinghuo Qibi Decoction combined with rehabilitation training in the treatment of autism spectrum disorder (ASD) of heart-liver fire hyperactivity pattern and its effects on inflammatory cytokines. Methods: A randomized controlled trial (RCT) was conducted. A total of 140 children with ASD of heart-liver fire hyperactivity pattern who attended our hospital and the Affiliated Hospital of Shaanxi University of Chinese Medicine between February 2022 and February 2025 were enrolled and divided into a study group and a control group according to a random number table, with 70 cases in each group. The control group received routine rehabilitation training (applied behavior analysis [ABA] and structured education), and the study group additionally received oral Qinghuo Qibi Decoction, with both groups treated for 12 weeks. The clinical efficacy, the Childhood Autism Rating Scale (CARS) and Psychoeducational Profile (Third Edition) for children with autism (C-PEP-3) scores before and after treatment, and changes in TNF-α, IL-1β, IL-6, IL-10 and lymphocyte subsets were compared between the two groups, and adverse reactions were recorded. Results: Three cases in the study group and four cases in the control group dropped out, and 133 cases were finally included. The total effective rate of the study group was 88.1%, which was higher than that of the control group (71.2%), with a statistically significant difference (P